Trials, tribulations and triumphs: Life and times of a sociologist - Oommen, T.K. (New Delhi Konark publishers Pvt. Ltd., 2018)
Trials, Tribulations and Triumphs showcases the details of life of T.K.Oommen, one of the most renowned sociologists in India, and maps his professional journey. Anecdotal in nature, the book provides insights into the functioning of the academic world through the discipline of sociology. It also discusses the social and political context of knowledge production and dissemination while bringing out the lack of professionalism among Indian sociologists.